Shaping the entrepreneurial mindset: Exploring effect of Self-Reflection and Lifelong learning: The mediating role of Self-Efficacy – A Survey Study - Yousif Riyadh Mahmood (Penerbit Jurnal Indonesia, 2026)
The paper examines entrepreneurial mind-set development, with a focus on the psychological processes and especially on self-reflection, lifelong learning, and self-efficacy. These internal drivers need to be comprehended in order to bring up a workforce that is proactive, flexible, and innovation-driven. The research took place in the AL-Qadisiyah University, Iraq and followed the quantitative research approach and relied on the reflective practice theory, Experiential learning, and social cognitive theory. To gather the data, Simple random sampling, was used, a prepared structured questionnaire was created with a 5-point Likert scale. The size of the sample was (110) participants. Alpha reliability was tested by Cronbach and Structural Equation Modeling (SEM) was used to test hypothesized effect. The findings indicated that Lifelong learning and self-reflection have a great influence on entrepreneurial mindset though, the standardized regression coefficient was (0.28 and 0.25, respectively). Also self-efficacy was mediated in this effect with standardized regression coefficient (0.236) which added to the combined effect (0.928) with significant level (0.01). These findings prove that self-efficacy mediates these associations partly and is a key psychological facilitator of entrepreneurial orientation. The research provides worthwhile contributions as it identifies the key psychological processes that make entrepreneurship develop. It also offers viable suggestions on how reflective and lifelong learning practices may be incorporated into professional training programs to increase self-efficacy and thinking entrepreneurially.